Socioeconomic Disparities in Maternal Health Facility Utilization at Hospital: Evidence from Indonesia's 2018 Basic Health Research - Yudi Adnan; Ranti Ekasari (Social Medicine)
Maternal and neonatal mortality remain critical issues, especially in developing countries like Indonesia. This study aims to analyze socioeconomic disparities in hospital utilization for childbirth in Indonesia using data from the 2018 Indonesian Basic Health Research. The study found that socioeconomic factors significantly influence hospital utilization by pregnant women, with higher socioeconomic status associated with higher hospital utilization. Urban residence, higher education level, employment status, and health insurance ownership positively correlated with hospital utilization. These findings highlight the need for targeted interventions to improve access and utilization of maternal health facilities, particularly among vulnerable socioeconomic groups. The study contributes to the literature by providing new insights into socioeconomic disparities in hospital utilization for childbirth. This can inform policymakers and health practitioners in improving maternal health in Indonesia